Perlindungan Hukum Terhadap Konsumen TransportasiJasa Ojek Online - Imam Syafei Wahid M; Suryati; Wiwin Mochtar Wiyono (Wijayakusuma Law Review, 2019)
To find out the legal reasoning of the judge in deciding the Marriage Dispensation Request in the decisionNumber: 0122 / Pdt.P / 2018 / PA.Pwt, To achieve this goal the author uses a Normative Juridical approach,Research specifications are Normative Data presentation methods are presented in the form of descriptionswhich are grouped and then arranged systematically. Based on the results of the research and discussion in thedecision Number: 0122 / Pdt.P / 2018 / PA.Pwt, it can be seen that the legal basis of judges in providingMarriage Dispensation is based on the reasons the two have long had a relationship, love each other, are veryfamiliar and have engaged even if the applicant's child has been pregnant for 2 months, then it has beenproven that the Petitioner's child is mature enough and mature to settle in. In addition, both of them are single,there is no relationship, not so that there are no barriers to marriage, and the applicant's family and parents ofprospective husbands have blessed the marriage plan. If the request for dispensation is not granted, it is fearedthat things will happen that are not desirable / violate religious norms, and for the good of prospectivechildren who are being conceived by the prospective bride. The provisions and principles of marriage law havebeen fulfilled as stipulated in Article 7 of Law No. 1/1974 Jo Article 15 up to Article 18 and Article 39Compilation of Islamic Law and in line with the Qaidah Fiqhiyah, (which in Indonesian means: "rejectingobedience takes precedence over priority"), which means that preventing evil must first sought before doinggood.